2019
DOI: 10.3233/jad-190204
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Magnetite- and Iron-Rich Pollution Nanoparticles: Potential Neurotoxicants and Environmental Risk Factors for Neurodegenerative Disease, Including Alzheimer’s Disease

Abstract: Fewer than 5% of Alzheimer's disease (AD) cases are demonstrably directly inherited, indicating that environmental factors may be important in initiating and/or promoting the disease. Excess iron is toxic to cells; iron overload in the AD brain may aggressively accelerate AD. Magnetite nanoparticles, capable of catalysing formation of reactive oxygen species, occur in AD plaques and tangles; they are thought to form in situ, from pathological iron dysfunction. A recent study has identified in frontal cortex sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 92 publications
2
74
0
1
Order By: Relevance
“…The authors also emphasized the brain substrates supporting dual-task gait performance in amnestic and non-amnestic MCI subtypes were different, a key finding potentially very relevant for our MMC populations with evolving cognitive domain deficits and significant differences in PM 2.5 exposures and portals of entry of fine PM and nanoparticles to the brain. 36 , 37 , 72 , 96 , 105 , 106 Beauchet et al, 107 put forward a biologically plausible explanation for the correlation between greater subvolumes of the somatosensory cortex and hippocampus reported in fallers compared to non-fallers: a possible brain compensatory mechanism involving spatial navigation and integration of sensory information. Indeed, in explaining increased gain in the auditory pathway (measured as brainstem auditory evoked potentials) in MMC residents we strongly supported compensatory plasticity, neuroinflammation, and AD continuum as strong players in MMC residents.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also emphasized the brain substrates supporting dual-task gait performance in amnestic and non-amnestic MCI subtypes were different, a key finding potentially very relevant for our MMC populations with evolving cognitive domain deficits and significant differences in PM 2.5 exposures and portals of entry of fine PM and nanoparticles to the brain. 36 , 37 , 72 , 96 , 105 , 106 Beauchet et al, 107 put forward a biologically plausible explanation for the correlation between greater subvolumes of the somatosensory cortex and hippocampus reported in fallers compared to non-fallers: a possible brain compensatory mechanism involving spatial navigation and integration of sensory information. Indeed, in explaining increased gain in the auditory pathway (measured as brainstem auditory evoked potentials) in MMC residents we strongly supported compensatory plasticity, neuroinflammation, and AD continuum as strong players in MMC residents.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the surplus of iron in neurodegenerative tissues appears as magnetic Fe 3 O 4 [73], hypothesis sustained by elevated concentration of Fe 3 O 4 detected in samples of Alzheimer's disease tissue [74]. Recently, brain magnetite nanospheres were identified in human subjects and were consistent with an external, rather than an endogenous, source [35,36]. Their presence demonstrates that externally sourced iron-bearing NPs can reach the brain, where they result in hazard to human health.…”
Section: Discussionmentioning
confidence: 99%
“…Airborne magnetite pollution particles (~200 nm in size) can access the brain also directly via the olfactory and/or trigeminal nerves, bypassing the BBB. Given their toxicity, abundance in roadside air, and nanoscale dimensions, traffic-derived magnetite pollution nanoparticles may constitute a chronic and pernicious neurotoxicant, and hence an environmental risk factor for Alzheimer's disease, for large population numbers globally [36], but even for children due to well recognized special susceptibility of the developing nervous system to environmental toxins [37,38]. Several evidences regarding to methylmercury, lead, alcohol, organophosphates indicate that the nature and severity of the brain function disruption depend on when the exposure occurred and the duration and concentration of neurotoxicants which may result in disorders that can be evident immediately after exposure as well as emerge later in life [39].…”
Section: Introductionmentioning
confidence: 99%
“…The primary source of magnetic pollution particles in the human brain and heart is assumed to be roadside air pollution arising from vehicle combustion and frictional brake-wear, and secondarily from industry and coal-fired power plants [72,135,139]. However, it is more likely that coal combustion products including coal fly ash are the primary source of these spherical magnetic particles, with a secondary contribution from vehicle (especially diesel) emissions.…”
Section: Sources Of Magnetic Nanoparticlesmentioning
confidence: 99%